Highlights in Practical Applications of Agents and Multiagent Systems 9th International Conference on Practical Applications of Agents and Multiagent Systems - Pérez, Javier Bajo.; Corchado, Juan M.; Moreno, María N.; Julian, Vicente; Mathieu, Philippe; Canda-Bago, Joaquin; Ortega, Alfonso; Caballero, Antonio Fernández; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
AAMS, the International Conference on Practical Applications of Agents and Multi-Agent Systems is an evolution of the International Workshop on Practical Applications of Agents and Multi-Agent Systems. PAAMS is an international yearly tribune to present, to discuss, and to disseminate the latest developments and the most important outcomes related to real-world applications. It provides a unique opportunity to bring multi-disciplinary experts, academics and practitioners together to exchange their experience in the development of Agents and Multi-Agent Systems.   This volume presents the papers that have been accepted for the 2011 edition in the special sessions: Special Session on Agents Behaviours for Artificial Markets, Special Session on Multi-Agent Systems for safety and securit, Special Session on Web Mining and Recommender Systems, Special Session on Adaptative Multi-Agent System, Special Session on Integration of Artificial Intelligence Technologies in Resource-Constrained Devices, Special Session on Bio-Inspired and Multi-Agents Systems: Applications to Languages and Special Session on Agents for smart mobility.
Electronic reproduction.
Keywords: Intelligent agents (Computer software) -- Congresses; Artificial intelligence -- Congresses; Multiagent systems -- Congresses; Electronic book